INVESTIGATING THE ROLE OF CONVENIENCE MOTIVATION IN SHAPING REPURCHASE INTENTION OF BEAUTY PRODUCTS VIA TIKTOK AFFILIATE MARKETING IN INDONESIA: - - Krisnata, Diva Skesya; Sidharta, Helena (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The rapid expansion of TikTok Shop has transformed social commerce in Indonesia, yet consumer retention—particularly in beauty product purchases—remains a challenge as most users make impulse-driven first purchases but do not consistently buy again. This gap highlights the need to understand whether convenience alone is sufficient to influence long-term consumer behavior. This study examines how convenience motivation shapes repurchase intention within the TikTok Affiliate ecosystem and evaluates the mediating role of customer satisfaction. A quantitative approach was applied using PLS-SEM with 205 Indonesian TikTok users who had purchased beauty products through affiliate links. The results show that convenience motivation significantly enhances customer satisfaction, indicating that seamless navigation and effortless purchasing contribute to positive user experiences. However, convenience has a weaker direct influence on repurchase intention, suggesting that ease of use alone does not guarantee loyalty in a highly dynamic beauty market. Customer satisfaction emerges as a key mechanism that connects convenience with repeat purchase behavior, demonstrating a significant mediating effect. These findings contribute to a deeper understanding of how functional simplicity and emotional fulfillment jointly drive consumer decisions in social commerce. The study offers practical insights for brands and creators to focus not only on providing convenience but also on enhancing satisfaction through credible communication, engaging content, and consistent product value.